Monocyte distribution width enhances the detection of infection in patients after primary percutaneous coronary intervention - Sheng-Feng Lin; Hui-An Lin; Peter C. Hou; Hung-Wei Tsai; Sen-Kuang Hou (PLoS ONE, 2025)
Background Monocyte distribution width (MDW) may serve as an infection marker in acute myocardial infarction (AMI) patients undergoing primary percutaneous coronary intervention (PCI), where infection rates range from 2.4% to 16.6%. We evaluated the association of increased MDW levels with infection occurrence and to assess MDW-based models for predicting infection risk and prolonged hospital length of stay (LOS) ≥ 7 days. Methods and results This retrospective cohort study included AMI patients undergoing PCI at a Taiwanese tertiary teaching hospital from January 1, 2020, to September 30, 2021. Logistic regression models incorporating MDW, Quick Sequential Organ Failure Assessment (qSOFA) score, age, and C-reactive protein (CRP) levels were compared to the Canada Acute Coronary Syndrome (C-ACS) score and stress hyperglycemia ratio (SHR). Among 252 patients, 12.7% developed infections, a rate that falls within the expected range. Infections were more frequent among patients with LOS ≥ 7 days (42.9% vs. 1.1%). A three-parameter model (qSOFA score ≥2, age ≥ 65, and MDW ≥ 20) demonstrated good performance for new infection (AUC: 0.834) and LOS ≥ 7 days (AUC: 0.714). Adding CRP ≥ 2 mg/dL improved predictions for infection (AUC: 0.909) and LOS ≥ 7 days (AUC: 0.798), outperforming the C-ACS score (AUC: 0.807) and SHR (AUC: 0.784). Conclusion MDW emerges as a promising biomarker for assessing the risks of infection and prolonged hospital LOS in patients with AMI. Its early use may facilitate timely clinical interventions, including earlier initiation of antibiotic therapy.